2012
DOI: 10.1126/science.1215106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mimicry Regulates ABA Signaling by SnRK2 Kinases and PP2C Phosphatases

Abstract: Abscisic acid (ABA) is an essential hormone for plants to survive environmental stresses. At the center of the ABA signaling network is a subfamily of type 2C protein phosphatases (PP2Cs), which form exclusive interactions with ABA receptors and subfamily 2 Snfl-related kinase (SnRK2s). Here, we report a SnRK2-PP2C complex structure, which reveals marked similarity in PP2C recognition by SnRK2 and ABA receptors. In the complex, the kinase activation loop docks into the active site of PP2C, while the conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
419
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 490 publications
(431 citation statements)
references
References 34 publications
7
419
2
3
Order By: Relevance
“…As shown in Fig. 3f, the structure of HAB1.1 was similar to that described in a previous report 10 . Surprisingly, the predicted structure of HAB1.2 was dramatically changed.…”
Section: Hab1 Undergoes Aba-controlled As During Early Developmentsupporting
confidence: 87%
See 3 more Smart Citations
“…As shown in Fig. 3f, the structure of HAB1.1 was similar to that described in a previous report 10 . Surprisingly, the predicted structure of HAB1.2 was dramatically changed.…”
Section: Hab1 Undergoes Aba-controlled As During Early Developmentsupporting
confidence: 87%
“…Thus, the immediate question is how this occurs and what the physiological role in plant adaptation is. It is known that in the absence of ABA, the 1:1 interaction of HAB1 and SnRK2.6 switches ABA signalling off 10 . In contrast, the binding of HAB1 by PYLs at the same ratio and in the presence of ABA turns ABA signalling on [5][6][7] .…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations
“…In Arabidopsis protoplasts, PYR1 and PYLs 1-12 could release ABI1 inhibition of ABA-dependent activation of RD29B-LUC expression by the SnRK2 protein kinases such as OST1/SnRK2.6 [4]. Structural analysis revealed that the interaction between SnRK2.6 and HAB1 mimics the interaction between ABA-bound PYL2 and HAB1 [12]. PYLs can inhibit PP2C activity in the presence of ABA, and thereby activating SnRK2.6, which can phosphorylate slow anion channel1 (SLAC1) and activate SLAC1-mediated ion currents [13,14].…”
Section: Introductionmentioning
confidence: 99%